Nutrition and Culinary Acculturation to Turkish Cuisine of Profile of Low-Income Asylum Seekers in Ankara, Turkey: A Qualitative Study. (7th June 2021) - Kalyoncu, Zeynep; Terzioglu, Fusun; Kaptanoglu, Ilknur Yuksel
Abstract: Objectives: Since Turkey has the highest number of asylum seekers in the world due to massive immigration in the last 10 years, institutionalizing the immigration management has been a challenge. The aim of this study is to explore regular and irregular food assistance program recipient asylum seekers' experiences and perspectives about household nutrition and culinary acculturation to Turkish cuisine. Methods: A qualitative research has been carried out with asylum seeker parents who have been receiving cash-based assistance in Ankara in the form of Turkish Red Crescent Card, which is funded by the European Union. Thirty-one in-depth interviews were conducted with 16 mothers and 15 fathers from Syria, Iraq, Afghanistan, Iran, and Somalia. In the framework of the research, perceptions of how cash-based assistance and/or solely food aid supports their household nutrition; as well as experiences of parents, with a focus on how these programs affect their culinary acculturation were explored. Thematic analyses were conducted with using NVivo software program. Results: Cash-based assistance program with Turkish Red Crescent Card was found to be a key factor for the survival of the participants, especially after the COVID-19 pandemic. Yet, the allowances were highly insufficient and partially covering basic costs of living. NGOs' food aid was irregular and most of them were tied to religious institutions. Lack of exposure to Turkish culture and language, ethnic environmental presence, cultural limitations of the emigrated country, demanding eligibility requirements, health disparities, not being able to work legally, and perceived impermanence in Turkey were found to be the main themes that were identified by the thematic analyses. Since the effect of the program on nutrition and culinary acculturation could be ameliorated by further adjustments, a conceptual framework of food-related aid experiences of asylum seekers in Turkey was created. Conclusions: Although Turkish Red Crescent Card is an invaluable resource for the low-income asylum seeker families, Turkey needs to adapt its food assistance program towards asylum seekers. Funding Sources: The research was funded through a grant from the Atilim University's Starting Research Fund Program (Grant Number: ATU-BAD-1920-02).